2013
DOI: 10.1016/j.jksus.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of Muntingia calabura extracts against larvae and pupae of diamondback, Plutella xylostella (Lepidoptera, Plutellidae)

Abstract: The aim of the present study was to evaluate the insecticidal effects of hexane and ethanolic extracts of the flowers and fruits of Muntingia calabura against diamondback moth, Plutella xylostella. The leaf disc immersion methodology was carried out to assess the insecticidal effects on the larvae and pupae as well as duration of the larval phase following feeding of the first instar larvae of diamondback on the treated leaf discs for 72 h. All extracts were toxic to larvae and pupae of P. xylostella. The etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
2
18
0
4
Order By: Relevance
“…grows naturally in Central America and was introduced to Brazil as a decorative tree (Bandeira et al, 2013). grows naturally in Central America and was introduced to Brazil as a decorative tree (Bandeira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…grows naturally in Central America and was introduced to Brazil as a decorative tree (Bandeira et al, 2013). grows naturally in Central America and was introduced to Brazil as a decorative tree (Bandeira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Muntingia calabura Linn. grows naturally in Central America and was introduced to Brazil as a decorative tree (Bandeira et al, 2013). Currently, this plant is well adapted in Brazil due to the favourable weather conditions and soil properties (Lopes et al, 2002;Figueiredo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As part of a systematic study on the insecticidal potential of the medicinal flora growing in the state of Pernambuco (Bandeira et al, 2013;Pereira et al, 2009), the objective of this work was to evaluate the potential of ethanolic extracts prepared from the stems and leaves of C. rhamnifolius, C. jacobinensis, C. sellowii and C. micans. on the development and survival of P. xylostella.…”
mentioning
confidence: 99%
“…Studies involving plant extracts with medicinal properties have reported insecticidal properties such as mortality (Bandeira et al, 2013;Mishra & Singh, 2014;Peres et al, 2017) and feeding deterrence (Chandrashekharaiah et al, 2015;Couto et al, 2016); Deformities in adults, pupae and larvae of Plutella xylostella (Peres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%